2012
DOI: 10.1097/sla.0b013e318235d9e6
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Activated Protein C in Early Coagulopathy and Later Organ Failure, Infection and Death in Trauma Patients

Abstract: Background Recent studies have identified an acute traumatic coagulopathy that is present on admission to the hospital and is independent of iatrogenic causes. We have previously reported that this coagulopathy is due to the association of severe injury and shock and is characterized by a decrease in plasma protein C levels. Whether this early coagulopathy and later propensity to infection, MOF and mortality are associated with the activation of protein C pathway has not been demonstrated and constitutes the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
228
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(238 citation statements)
references
References 32 publications
5
228
1
4
Order By: Relevance
“…In addition, by binding PAI-1 and de-repressing t-PA, it may activate fibrinolysis [3,5,29]. This mechanism is plausible but problematic due to the kinetics of the reactions.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, by binding PAI-1 and de-repressing t-PA, it may activate fibrinolysis [3,5,29]. This mechanism is plausible but problematic due to the kinetics of the reactions.…”
Section: Pathophysiologymentioning
confidence: 99%
“…These processes are reflected in the findings of observational clinical studies that show reduced clotting factor and physiological anticoagulant levels [21][22][23], high thrombin generating capacity [3,4,21,[24][25][26] and reduced platelet counts [27,28] Overall, these data indicate a consumptive coagulopathy. The most depleted coagulation factors are fibrinogen and factor V [22,28], which are likely consumed in part by activated Protein C or free plasmin [29,30], although the relative importance of these proteases in reducing factor levels remains unknown. Thrombin is the key effector molecule in haemostasis; its generation not only converts fibrinogen to fibrin but, like a cytokine, it also activates platelets, leucocytes and endothelium.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, early fibrinolysis, platelet dysfunction, clotting factor inactivation and depletion, were described in acute traumatic coagulopathy [18][19][20] . To approach those multiple conditions, pharmacological agents have been incorporated in the management of coagulopathy 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the coagulation abnormalities associated with TBI, which show a combination of both hypocoagulable and hypercoagulable states (14). It has also been hypothesized that the trauma causes local release of tissue factor from the injured neurons, which is associated with activation of the protein C pathway, thus triggering the release of anticoagulant mediators (15). Borgman et al (16) found both admission base deficit < 8 and INR > 1.8 to be independently associated with mortality, and proposed that a score based on these predictors of adverse outcome ("BIG" score: base deficit + [2.5 x INR] + [15-GCS score]) may more accurately predict mortality in pediatric trauma patients than scoring systems currently in use.…”
Section: Evaluation Of Volume Status In Pediatric Trauma Patientsmentioning
confidence: 99%